Farm Brokers Conference, 1962 (1962)
Dr. Dan C. Chase, head of the Agricultural Business Management Department, hands a folder to to a group of men at the 4th annual Institute of Farm Brokers Educational Conference. Trends in agriculture and new developments in farm mechanization were topics discussed at the annual conference.